1997
DOI: 10.1007/s004390050365
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal and oropharyngeal cancer, and alcohol dehydrogenase 3 and glutathione S-transferase M1 polymorphisms

Abstract: In this study the GSTmu phenotype and ADH genotype at the ADH3 locus were investigated in a group of 39 alcoholic men with upper respiratory/digestive tract cancer: 21 with oropharyngeal cancer and 18 with laryngeal cancer. The results are compared with those of a control group of 37 alcoholic men without alcohol-related medical complications. Of the control subjects, 48% were found to be GSTmu deficient [GSTmu(-)] and 19% carried the ADH(3)1/ADH(3)1 genotype. In the laryngeal cancer patients, a significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 40 publications
(45 reference statements)
5
79
1
4
Order By: Relevance
“…Another study in France of 21 alcoholic oropharyngeal cancer cases compared to 37 alcoholic controls suggested overall higher OC risk was associated with the ADH 3 1-1 genotype, but this finding was not statistically significant and an alcohol interaction test could not be performed because both cases and controls were heavy alcohol drinkers. 42 Our study in Greece did not exclude subjects with liver damage and in this respect is similar to the Puerto Rico study. Evidence of an ADH 3 SNP interaction with alcohol consumption and OC risk similar to that observed in our study has recently been found in a study of 351 OC cases and 541 controls from western Washington State in the U.S. (S.M.…”
Section: Discussionmentioning
confidence: 59%
“…Another study in France of 21 alcoholic oropharyngeal cancer cases compared to 37 alcoholic controls suggested overall higher OC risk was associated with the ADH 3 1-1 genotype, but this finding was not statistically significant and an alcohol interaction test could not be performed because both cases and controls were heavy alcohol drinkers. 42 Our study in Greece did not exclude subjects with liver damage and in this respect is similar to the Puerto Rico study. Evidence of an ADH 3 SNP interaction with alcohol consumption and OC risk similar to that observed in our study has recently been found in a study of 351 OC cases and 541 controls from western Washington State in the U.S. (S.M.…”
Section: Discussionmentioning
confidence: 59%
“…There may also be an association between the homozygous ADH3*1 genotype and risk of oral cancer (Coutelle et al 1997;Harty et al 1997); however, this gene is not reported to be active in the oral mucosa (Dong et al 1996). Epidemiological evidence points to an increased risk of rectal cancer in heavy drinkers.…”
Section: Alcohol Dehydrogenasementioning
confidence: 99%
“…58 Elevated odds (OR 5.3, 95% CI, 1.0-28.8) of oral cancer in association with the ADH1C*1-1 genotype were observed only among heavy alcohol users (57 drinks per week) in Puerto Rico 59 and among alcoholics in Germany 60 and France. 55,61 However, contradictory conclusions were reported in studies conducted in the U.S. 62,63 and Greece, 64 in which the ''slow metabolizing'' ADH1C*2-2 genotype was associated with increased risk for HNSCC among heavy drinkers. Other studies reported no associations between ADH genotype and risk of HNSCC.…”
Section: Alcohol Consumption and Metabolismmentioning
confidence: 99%